2006
DOI: 10.1080/10550490500419011
|View full text |Cite
|
Sign up to set email alerts
|

Return to Smoking Following a Smoke‐Free Psychiatric Hospitalization

Abstract: This study examined the smoking behaviors and motivations of 100 patients hospitalized in a smoke-free psychiatry unit. The sample averaged nineteen cigarettes per day and had a history of repeated failed quit attempts, yet 65% expressed interest in quitting. During hospitalization, nicotine replacement was provided to 70% of smokers to manage nicotine withdrawal. Provider counseling for smoking cessation, however, was rare, and all patients returned to smoking within five weeks of hospital discharge. The inpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
147
2
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(162 citation statements)
references
References 30 publications
6
147
2
7
Order By: Relevance
“…61,62 Nonetheless, similar data were reported in another study, where 24% of acute-care psychiatric inpatient smokers endorsed preparing to quit. 41 Further, an earlier Canadian study looking at a more specific group of out-patients with schizophrenia confirmed that motivation for smoking cessation can be substantial (42% in contemplation or above). 49 However, our percentage of action-oriented patients might have been inflated by the RTQL classifying patients who are cutting down, rather than who have stopped, as being in action.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…61,62 Nonetheless, similar data were reported in another study, where 24% of acute-care psychiatric inpatient smokers endorsed preparing to quit. 41 Further, an earlier Canadian study looking at a more specific group of out-patients with schizophrenia confirmed that motivation for smoking cessation can be substantial (42% in contemplation or above). 49 However, our percentage of action-oriented patients might have been inflated by the RTQL classifying patients who are cutting down, rather than who have stopped, as being in action.…”
Section: Discussionmentioning
confidence: 91%
“…It is possible that published outcomes from inpatient smoking bans, generally reported to produce less than expected increases in agitation, especially when nicotine withdrawal is treated, have swayed mental health care providers toward believing that smoking cessation treatment may be possible in this setting. 53,68 Although hospital smoking bans by themselves appear to have a limited impact on smoking cessation 40,41 (such as the one in effect throughout the Calgary Health Region since 2002 69 ), its presence might have influenced people to report higher motivation and staff to be more aware of addressing quitting. More efficacious and better tolerated medications for smoking cessation may also provide the impetus for smoking cessation to gain greater priority in inpatient psychiatric care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In prospective studies, tobacco use is one of the strongest predictors of suicidal behavior in youth and adults, even after controlling for depressive symptoms, other substance use, and prior suicidal behavior (Breslau, Schultz, Johnson, Peterson, & Davis, 2005;Oquendo et al, 2004). In regions where smoking is greatly restricted, heavy smokers with mental illness may find it difficult to participate socially, leading to isolation (Prochaska, Fletcher, Hall, & Hall, 2006).…”
mentioning
confidence: 99%
“…95 Smoking bans alone will not produce long-term abstinence. 100 A humane policy would provide patients with access to nicotine while in hospital-e.g., by providing nicotine replacement therapy, counselling, and other pharmacotherapy on admission. Cessation support should also be provided at discharge and on return to the community.…”
Section: Smoking Bans In Psychiatric Unitsmentioning
confidence: 99%